Analysis of working capital management in food and beverage sub-sector companies during the covid-19 period: A financial performance perspective of ROA - Muni, Wilhelmina; Sanga, Marianus Hendrilensio; Seran, Patrisius; Takena, Rizka Angela (Institute of Computer Science (IOCS), 2025)
The food and beverage sub-sector is an integral part of the global economy and has a significant impact on economic growth. However, the COVID-19 pandemic has brought unprecedented challenges to this industry. It was recorded that in 2020, the Net Profit Margin of the food and beveerage sub-sector experienced a significant decline compared to the Net Profit Margin of other manufacturing sub-sectors. In this study, profitability is measured using Return on Assets (ROA). ROA is a ratio that shows the return on the total assets used in a company. ROA is also a measure of management's effectiveness in managing its investments. An analysis of Return on Assets (ROA) can provide valuable insights into understanding how working capital management in food and beverage sub-sector companies performed during the COVID-19 pandemic. In this context, ROA can provide an overview of how well companies were able to optimize their assets to generate profits, given the changes in market dynamics and challenges faced during the pandemic